KEBERLAKUAN ASAS EQUALITY BEFORE THE LAW BAGI PEJABAT PELAKSANA KEBIJAKAN PENANGANAN COVID-19 - Yunianto, Beny; Michael, Tomy (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe aim of the research is to offer novelty regarding the constitualism of the Government Regulation in Lieu of Law regarding Covid-19 which has now become a Law. This study uses a normative research method, with a focus on solving issues (problems) based on legal principles, legal rules, as well as on recognized legal expert opinion or doctrine. Through this research, the researcher offers that the perppu which has now become a law must be declared invalid or revoked because it is unconstitutional. As is well known, the Government issued Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling Pandemic Corona Virus Disease 2019 (COVID-19) and / or in the Context of Facing Threats that Endanger the National Economy and / Or Financial System Stability, on March 31, 2020 (now Law Number 2 of 2020, on May 18, 2020). In Article 27 paragraph (1), paragraph (2), and paragraph (3) it is stated that there are parties who have